The Influence of Mind Mapping Strategy and Achievement Motivation on Learning Outcomes of Sacrificial Materials in MIS Raudlatul Uluum - Ritonga, Asnil Aidah; Abdillah, Abdillah; Ilba, Hafridah (Budapest International Research and Critics University, 2020)
The objectives of this study were: (1) to determine the effect of learning strategies on learning outcomes (2) to determine the effect of achievement motivation on learning outcomes, (3) to determine differences in learning outcomes, (4) to determine differences in learning outcomes between students and students. High achievement motivation with low motivation, and (5) to determine the interaction of learning strategies and achievement motivation on student Jurisprudence learning outcomes. The research method used is quantitative methods with a quasi-experimental approach. The study population consisted of four classes, namely V-1, V-2 and V-3 and V-4. Through the cluster random sampling technique, 1 class was selected as the experimental class which was taught using mind mapping strategies and 1 control class which was taught using the expository strategy. The data collection instruments were questionnaires and tests and data analysis techniques used two-way analysis of variance. The findings of the study show: (1) there is an effect of learning strategies on students' Jurisprudence learning outcomes, (2) there is an effect of achievement motivation on the results of